Effect of Health Education with Spinal Anesthesia Video to Lower Pre-Anesthesia Anxiety in Genteng General Hospital, Banyuwangi, East Java, Indonesia - Katmini, Katmini; Suryanto, Suryanto; Puspitasari, Yenny (Indonesian Journal of Medicine, 2022)
Background: Spinal anesthesia is an anesthetic method by injecting local analgesic drugs into the subarachnoid space in the lumbar region. The purpose of the study was to analyze the effect of health education with spinal anesthesia videos on anxiety in pre-anesthesia in the operating room of the Genteng Regional General Hospital Banyuwangi.Subjects and Method: A quasi experiment study was conducted in Genteng General Hospital, Banyuwangi, East Java, in August 2022. A sample of 15 patients who underwent surgery under spinal anesthesia was selected by incidental sampling. The dependent variable is anxiety. The independent variables were video educational intervention. Anxiety was measured by Anxiety Analog Scale (AAS). Other variables were collected by questionnaire. The difference test in the paired group was examined using paired t-test.Results: Anxiety level after intervention (Mean= 180; SD= 80.84) was lower than before (Mean= 305; SD= 75.12) with p<0.001.Conclusion: Video of spinal anesthesia intervention lower anxiety in pre anesthesia surgery.Keywords: anxiety, spinal video, pre anesthesia, spinal anesthesia, health educationCorrespondence: Katmini. STRADA Indonesian Institute of Health Sciences. Jl. Manila No. 37, Kediri, East Java 64123, Indonesia. Email: katminitini@gmail.com. Mobile: 0823-3466-2921.Indonesian Journal of Medicine (2022), 07(03): 306-312https://doi.org/10.26911/theijmed.2022.07.03.07